Pengaruh Hukum Islam dan Dinamika Sosial pada Masa Khulafaur Rasyidin dan Fase Mulkan Jabariyyah - Hasna Amiroh Malda; Muhammad Husni Abdulah Pakarti; Diana Farid; Ais Surasa; Ulummudin Ulummudin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Islamic law has a close relationship with the evolving social dynamics within Muslim societies. Social, cultural, and political changes demand flexibility in the application of Islamic law to remain relevant. This study employs a historical approach and descriptive analysis, focusing on two major phases in Islamic history: the Khulafaur Rasyidin phase and the Mulkan Jabariyyah phase. Data were collected through literature reviews of various primary and secondary sources. The findings indicate that Islamic law can adapt to social changes through the mechanisms of ijtihad and tajdid. However, its application must consider social, cultural, and historical contexts to avoid misinterpretation. Islamic law is not a static entity but a dynamic and responsive system that evolves with societal changes. With the right contextual approach, Islamic law can remain relevant in modern Muslim societies.